Quantitative estimating size of deep defects in multi-layered structures from eddy current NDT signals using improved ant colony algorithm - Bo Ye; Ming Li; Gefei Qiu; Jun Dong; Fang Zeng; Tanghua Yang; Biao Bai (Fracture and Structural Integrity)
Detection and quantitative estimation of deep defects in multi-layered structures is an essential task in a range of technological applications, such as maintaining the integrity of structures, enhancing the safety of aging aircraft, and assuring the quality of products. A novel approach to accurately quantify the two-dimensional axisymmetric deep defect size from eddy current nondestructive testing (NDT) signals is presented here. The method uses a finite element forward model to simulate the underlying physical process and an improved ant colony algorithm (IACA) to solve the inverse problem. Experiments are carried out. The performance comparison between the IACA method and the least square method is shown. The comparison results demonstrate the feasibility and validity of the IACA method. Between them, the IACA method gives a better estimation performance than the least square method at present.